2020
DOI: 10.1007/s10942-020-00364-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Metacognition in Binge Eating Disorder

Abstract: Research has shown that metacognition may play a role in problem eating. In this study we explored whether aspects of metacognition are relevant to the understanding of binge eating in patients with Binge Eating Disorder. We aimed to ascertain: (1) the presence of metacognitive beliefs about binge eating; (2) the goal of, and stop signal for, binge eating; and (3) the impact of binge eating on self-consciousness. Ten Binge Eating Disorder patients took part in the study and were assessed using the metacognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Taken together these results confirm the notion that metacognitive beliefs could be implicated in eating disorders and eating behaviours. Our results are consistent with a previous study (Sun et al, 2017) which pointed out that, as in other psychopathological presentations, negative beliefs about worry, beliefs about the need to control thoughts, cognitive confidence and cognitive self‐consciousness are most strongly associated with eating disorders (Hamonniere & Varescon, 2018; Rogier et al, 2020; Palmieri et al, 2020; Spada et al, 2013; Wells & Matthews, 1994, 1996). On the other hand, we also found that patients differ among each other on positive and negative beliefs about worry as well as in levels of cognitive confidence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Taken together these results confirm the notion that metacognitive beliefs could be implicated in eating disorders and eating behaviours. Our results are consistent with a previous study (Sun et al, 2017) which pointed out that, as in other psychopathological presentations, negative beliefs about worry, beliefs about the need to control thoughts, cognitive confidence and cognitive self‐consciousness are most strongly associated with eating disorders (Hamonniere & Varescon, 2018; Rogier et al, 2020; Palmieri et al, 2020; Spada et al, 2013; Wells & Matthews, 1994, 1996). On the other hand, we also found that patients differ among each other on positive and negative beliefs about worry as well as in levels of cognitive confidence.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, since the publication of the review by Sun et al (2017), additional studies have been published (it also worth noting that a few earlier studies were not been included in Sun and colleagues' review). Despite the increasing interest in this area of research (Palmieri et al, 2020; Robertson & Strodl, 2020), no study, to date, has provided a synthesis of all research that has explored the potential differences or similarities in metacognitive beliefs across different eating disorders diagnoses. It may be worthy to explore these differences or similarities because literature has shown, for example, that Anorexia Nervosa patients report higher levels of positive and negative metacognitive beliefs about worry than bulimic patients (Sapuppo et al, 2018; Vann et al, 2014), while bulimic patients present with higher levels positive beliefs about worry than patients with an Eating Disorder Not Otherwise Specified (Olstad et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Where desire thinking may be problematic for cravings and associated psychopathology, it is metacognitions that precede and maintain these thinking styles. These approaches are consistent with metacognitive therapy for other addictive behaviours (Caselli et al, 2018;Palmieri et al, 2020;Spada et al, 2013;Wells, 2009), such as therapy that aims to reduce the negative impact of these processes (e.g., attention training; Wells, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…Metacognitions have been found to play a significant role in predicting distress, independently of other established constructs, across a broad variety of psychiatric disturbances, such as psychosis (Tas et al, 2014), depression (Papageorgiou & Wells, 2001), generalized anxiety disorder and panic disorder (Aydın et al, 2019), obsessive–compulsive disorder (Cucchi et al, 2012), eating disorders (Palmieri et al, 2021), problematic social media use (Balıkçı et al, 2020) and problematic Internet use (Spada & Marino, 2017). There is notable paucity, however, of studies investigating the influence of metacognitions in both cyberbullying and cybervictimization.…”
Section: Introductionmentioning
confidence: 99%